2022
DOI: 10.1101/2022.02.23.22271388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of Long Covid in people infected with SARS-CoV-2 after two doses of a COVID-19 vaccine: community-based, matched cohort study

Abstract: Background: It is unclear whether receiving two COVID-19 vaccinations before SARS-CoV-2 infection reduces the risk of developing Long Covid symptoms. We examined whether the likelihood of symptoms 12 weeks after infection differed by vaccination status. Methods: We included COVID-19 Infection Survey participants aged 18-69 years who tested positive for SARS-CoV-2 between 26 April 2020 and 30 November 2021; we excluded participants who, before their first test-confirmed infection, had suspected COVID-19 or Lon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 12 publications
4
27
0
2
Order By: Relevance
“…For the 'vaccine -infection -long COVID' studies, the impact of vaccine on long-COVID symptoms was presented as odds ratio (OR), adjusted odds ratio (aOR), and hazards ratio (HR). Two articles 23,24 used HR, two 19 20 used purely OR, one 22 used aOR, and another 21 used both aOR and OR for expressing differences in long-COVID development between vaccinated and nonvaccinate people.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For the 'vaccine -infection -long COVID' studies, the impact of vaccine on long-COVID symptoms was presented as odds ratio (OR), adjusted odds ratio (aOR), and hazards ratio (HR). Two articles 23,24 used HR, two 19 20 used purely OR, one 22 used aOR, and another 21 used both aOR and OR for expressing differences in long-COVID development between vaccinated and nonvaccinate people.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Therefore, the mass media reports were misleading to the public, which should have been avoided as much as possible. Regarding the effectiveness of vaccination against long COVID-19, two studies by Ayoubkhani et al demonstrated that people who completed two doses of vaccine were less likely to develop long-term sequelae after being infected with COVID-19 ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tab. 1), wovon 7 zeigen, dass die COVID-19-Impfung mit einem reduzierten Long-COVID-Risiko assoziiert ist, wobei dies in 6 Fällen [19][20][21][22][23][24][25] für die vollständige Impfung und in einem Fall für die Einfachimpfung zutraf [25]. Zwei dieser Studien unterschieden nicht, ob die Impfung vor oder nach Infektion stattgefunden hat [24,25].…”
Section: Covid-19-impfung Zur Prävention Von Long-covidunclassified
“…Eine einmalige Impfung hatte keinen protektiven Effekt (aOR 1,00, 95 %-KI 0,66-1,49; [22]). Eine britische Studie ergab, dass eine zweimalige Impfung mindestens 2 Wochen vor SARS-CoV-2-Infektion mit einer 41 %igen Reduktion der Long-COVID-Wahrscheinlichkeit zum Zeitpunkt 12 Wochen nach Infektion assoziiert war: Long-COVID jeglichen Schweregrads aOR 0,59 (95 %-KI 0,50-0,69), aktivitäteneinschränkende Long-COVID aOR 0,59 (95 %-KI 0,48-0,73; [23]).…”
Section: Impfung Vor Sars-cov-2-infektionunclassified